1039 Health inequalities, work and access to social security of informal workers in latin america, africa and asia. (24th April 2018) - Solar, O; Bernales, P; Gonzalez, MJ; Riesco, A; Vives, A; Alamos, V
Abstract : Introduction: Around the world exist the expansion of the informal economy and traditionally people -working in the informal economy (WIE) do not have access to the established state-run healthcare systems. Understanding the barriers that explain the low participation of people-working informal economy in health systems and social security systems, providing social protection and eliminate obstacles to accessing care, should be viewed by governments as a strategy to improve the health of these workers. Methods: Develop baseline of information on the health and occupational health of informal workers and their access to health and social security systems in 6 countries of Africa, 6 of Asia and 12 countries of Latin America. The methodology included Case Studies were oriented to analyse access to health and social security, their employment and working conditions and their relationship to the characteristics of the countries´ economic structure. The Qualitative Studies Component collected the primary information based on the informal workers' perception The Core Indicators component aimed to build indicators on several domains and subdomains of informal work and health that are relevant, robust and comparable between countries, as well as to identify information gaps, based on the analysis of different country surveys. Result: People –WIE are women and men from different age groups – higher rate of work among eldest and youngest groups – and educational backgrounds levels, living in urban and rural areas; present in different industrial sectors –; strong positive association between a country's proportion of informal jobs and its statistics on productive years of life lost and disability-adjusted life years (DALYs); high burden of disease that affects informal workers. Discussion: The lack of evidence on this subject has been detrimental to the development of sound policies addressing access to health by people-WIE and their families.